The Effect of Net Interest Margin, Fee-Based Income, and Operating Expenses on Profitability in Banking Subsector Companies for the 2022-2024 Period - Natazya Deska Dila; Angga Permadi Karpriana (Jurnal Akuntansi, 2025)
Profitability reflects a company's ability to gain profits in a sustainable manner and is a benchmark for assessing financial health. This research is to analyze the influence of net interest margin (NIM), cost-based income (FBI) and operational cost efficiency (BOPO) on profitability as measured by ROA in banking subsector companies listed on the IDX. The total data sample is 105, with the sampling method namely purposive sampling. Data were analyzed using multiple linear regression techniques and processed using SPSS software. Partially, NIM positively and significantly influences ROA, FBI positively but not significantly influences ROA, and BOPO negatively and significantly influences ROA. Meanwhile, simultaneously, these three variables are proven to influence ROA significantly.